Licochalcone B Induces ROS-Dependent Apoptosis in Oxaliplatin-Resistant Colorectal Cancer Cells via p38/JNK MAPK Signaling - Ah-Won Kwak; Woo-Keun Kim; Seung-On Lee; Goo Yoon; Seung-Sik Cho; Ki-Taek Kim; Mee-Hyun Lee; Yung Hyun Choi; Jin-Young Lee; Jin Woo Park; Jung-Hyun Shim (MDPI AG, 2023)
Licochalcone B (LCB) exhibits anticancer activity in oral cancer, lung cancer, and hepatocellular carcinoma cells. However, little is known about its antitumor mechanisms in human oxaliplatin-sensitive and -resistant colorectal cancer (CRC) cells. The purpose of the present study was to investigate the antitumor potential of LCB against human colorectal cancer in vitro and analyze its molecular mechanism of action. The viability of CRC cell lines was evaluated using the MTT assay. Flow cytometric analyses were performed to investigate the effects of LCB on apoptosis, cell cycle distribution, reactive oxygen species (ROS), mitochondrial membrane potential (MMP) dysfunction, and multi-caspase activity in CRC cells. The results demonstrated that LCB induced a reduction in cell viability, apoptosis, G2/M cell cycle arrest, ROS generation, MMP depolarization, activation of multi-caspase, and JNK/p38 MAPK. However, p38 (SB203580) and JNK (SP600125) inhibitors prevented the LCB-induced reduction in cell viability. The ROS scavenger N-acetylcysteine (NAC) inhibited LCB-induced reduction in cell viability, apoptosis, cell cycle arrest, ROS generation, MMP depolarization, and multi-caspase and JNK/p38 MAPK activities. Taken together, LCB has a potential therapeutic effect against CRC cells through the ROS-mediated JNK/p38 MAPK signaling pathway. Therefore, we expect LCB to have promising potential as an anticancer therapeutic and prophylactic agent.